Contraception Selection, Effectiveness, and Adverse Effects: A Review - Teal, Stephanie; Edelman, Alison (JAMA : the journal of the American Medical Association, 2021)
Many women spend a substantial proportion of their lives preventing or planning for pregnancy, and approximately 87% of US women use contraception during their lifetime. Contraceptive effectiveness is determined by a combination of drug or device efficacy, individual fecundability, coital frequency, and user adherence and continuation. In the US, oral contraceptive pills are the most commonly used reversible method of contraception and comprise 21.9% of all contraception in current use. Pregnancy rates of women using oral contraceptives are 4% to 7% per year. Use of long-acting methods, such as intrauterine devices and subdermal implants, has increased substantially, from 6% of all contraceptive users in 2008 to 17.8% in 2016; these methods have failure rates of less than 1% per year. Estrogen-containing methods, such as combined oral contraceptive pills, increase the risk of venous thrombosis from 2 to 10 venous thrombotic events per 10 000 women-years to 7 to 10 venous thrombotic events per 10 000 women-years, whereas progestin-only and nonhormonal methods, such as implants and condoms, are associated with rare serious risks. Hormonal contraceptives can improve medical conditions associated with hormonal changes related to the menstrual cycle, such as acne, endometriosis, and premenstrual dysphoric disorder. Optimal contraceptive selection requires patient and clinician discussion of the patient's tolerance for risk of pregnancy, menstrual bleeding changes, other risks, and personal values and preferences. Oral contraceptive pills are the most commonly used reversible contraceptives, intrauterine devices and subdermal implants have the highest effectiveness, and progestin-only and nonhormonal methods have the lowest risks. Optimal contraceptive selection incorporates patient values and preferences.